The Grasping Hand Structural and Functional Anatomy of the Hand and Upper Extremity. - Gupta, Amit (Thieme Medical Publishers, Incorporated, 2021)
Anatomical guide leverages exceptional dissection images to elucidate the biomechanics of the hand and upper extremity The hand is a unique instrument that executes the commands of the brain and expresses the nuances of the mind. The Grasping Hand: Structural and Functional Anatomy of the Hand and Upper Extremity by Amit Gupta and Makoto Tamai is a state-of-the-art book that details the functions of the hand to feel, receive, gather, collect and hold, as well as the complex role that the whole upper extremity plays in enabling these actions. The anatomical structures intrinsic to these functio.